Analisis Penerapan ISAK 35 dalam Penggunaan Sango Professional Pada LSM Koalisi Rakyat untuk Keadilan Perikanan (KIARA) Jakarta - Rizki Hermaliani (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study aims to analyze the implementation of the Interpretation of Financial Accounting Standards (ISAK) 35 in the preparation of financial statements at the People's Coalition for Fisheries Justice (KIARA) NGO and to evaluate the effectiveness of the SANGO Professional accounting software. This research is motivated by the need to enhance transparency and accountability in the financial management of NGOs in accordance with applicable accounting standards. The research method used is descriptive qualitative, with primary data obtained through interviews and participatory observation. Secondary data were taken from KIARA's 2023 financial statements. The results show that KIARA has successfully implemented ISAK 35 in the preparation of its financial statements since 2022. The use of SANGO Professional has helped KIARA in recording financial transactions in a more structured and systematic manner. Additionally, this software facilitates the management of complex financial data, thereby minimizing recording errors. The conclusion of this study is that the implementation of ISAK 35 has improved the accuracy and transparency of KIARA's financial statements. SANGO Professional is effective in supporting financial management, but there is a need for feature enhancements to better support the optimal implementation of ISAK 35.